Mottakelse/mottakelse; Tilbakekomstene til den østerrikskungarske nordpolekspedisjonen, 1872-1874 - Schimanski, Johan; Spring, Ulrike (Nordlit, 2007)
This article investigates the welcoming receptions held on the return of the Austro- Hungarian Polar Expedition (1872-1874) as part of a Scandinavian and Central European discourse of the Arctic and of Arctic exploration. Also called the Payer-Weyprecht or Tegetthoff Expedition, it was subjected to a long series of such public celebrations on its way home to Austria-Hungary via Norway, Sweden and Germany. While our access to these celebrations is through written sources such as newspaper reports, the celebrations themselves are here seen as constituting a discourse primarily made up of performative and material elements. This discourse is formed by values such as heroism, national identities, local identities, class and gender. The article focuses on welcoming receptions in Bergen and in Vienna, exploring the central role of the explorers’ bodies and traces/recreations of the Arctic. It also follows connections between these celebratory receptions and the literary reception of the expedition in Christoph Ransmayr’s novel Die Schrecken des Eises und der Finsternis (1984). Parts of the argument have been developed further in ”Explorers’ Bodies in Arctic Mediascapes: Celebrating the Return of the Austro-Hungarian Polar Expedition in 1874”, Acta Borealia, 26.1 (2009), pp. 50-76, http://dx.doi.org/10.1080/08003830902951532.